Metabolic Engineering of Crocin Biosynthesis in Nicotiana Species - Ahrazem, Oussama; Zhu, Changfu; Huang, Xin; Rubio-Moraga, Angela; Capell, Teresa; Christou, Paul; Gómez-Gómez, Lourdes (Frontiers in Plant Science, 2022)
Crocins are high-value soluble pigments that are used as colorants and supplements, their presence in nature is extremely limited and, consequently, the high cost of these metabolites hinders their use by other sectors, such as the pharmaceutical and cosmetic industries. The carotenoid cleavage dioxygenase 2L (CsCCD2L) is the key enzyme in the biosynthetic pathway of crocins in Crocus sativus. In the present study, CsCCD2L was introduced into Nicotiana tabacum and N. glauca for the production of crocins. In addition, a chimeric construct containing the Brevundimonas sp. B-carotene hydroxylase (BrCrtZ), the Arabidopsis thaliana ORANGE mutant gene (AtOrMut) and CsCCD2L was also introduced into N. tabacum. Quantitative and qualitative studies on carotenoids and apocarotenoids in the transgenic plants expressing CsCCD2L alone showed higher crocin level accumulation in N. glauca transgenic plants, reaching almost 400 g/g DW in leaves, while in N. tabacum 36 g/g DW was obtained. In contrast, in N. tabacum plants co-expressing CsCCD2L, BrCrtZ and AtOrMut accumulated, 3.5-fold compared to N. tabacum plants only expressing CsCCD2L. Crocins with three and four sugar molecules were the main molecular species in both host systems. Our results demonstrate that the production of saffron apocarotenoids is feasible in engineered Nicotiana species and establish a basis for the development of strategies that may ultimately lead to the commercial exploitation of these valuable pigments for multiple applications.